2024
DOI: 10.1038/s41598-023-50721-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness is related to concentration performance in adolescents

Wolfgang Altermann,
Peter Gröpel

Abstract: The aim of this study was to test the relationship between physical fitness and attention in a sample of adolescents. The hypothesis was that the overall fitness as well as its single components (speed, endurance, strength, coordination, and flexibility) would be positively related to participants’ performance in a test of attention. Participants were adolescent students (N = 140) aged 15 to 18 years. Physical fitness was measured with the German Motor Test. Attention was assessed with the d2-Test of Attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The literature has reported that physical fitness can indeed facilitate brain maturation and CP [ 44 ]. Studies have also shown links between PA and different brain structures, which can lead to hypothesizing that PA may influence cognitive functions [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has reported that physical fitness can indeed facilitate brain maturation and CP [ 44 ]. Studies have also shown links between PA and different brain structures, which can lead to hypothesizing that PA may influence cognitive functions [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature has reported that physical fitness can indeed facilitate brain maturation and CP [ 44 ]. Studies have also shown links between PA and different brain structures, which can lead to hypothesizing that PA may influence cognitive functions [ 44 ]. PA has been consistently linked with enhanced CP [ 17 , 45 ]; hence, exercise during this important developmental stage can have an impact on neurological and cognitive outcomes [ 45 ].…”
Section: Discussionmentioning
confidence: 99%